Answer:
3/2.
Step-by-step explanation:
f(x)=2x+5 Finding the inverse:
y = 2x + 5
2x = y - 5
x = (y - 5)/2
So the inverse f-1(x) = (x - 5)/2
and f-1(8) = (8-5)/2
= 3/2.
9514 1404 393
Answer:
C, A, A
Step-by-step explanation:
In general, you ...
- identify the coefficients of one of the variables
- swap them, and negate one of them
- multiply the corresponding equations by the "adjusted" coefficients.
__
In problem 1, the x-coefficients are 8 and 2. A common factor of 2 can be removed so that we're dealing with the numbers 4 and 1. Assuming we want to multiply one of the equations by 1, leaving it unchanged, the value we want to multiply by will be -4. After we swap the coefficients, that multiplier is associated with equation 2:
multiply equation 2 by -4 . . . (eliminates x)
Likewise, the y-coefficients in problem 1 are -1 and 3. Again, if we want to multiply one of the equations by 1, leaving it unchanged, the coefficient we will change the sign of is -1 (becomes 1). After we swap the coefficients, the multiplier 3 is associated with equation 1:
multiply equation 1 by 3 . . . (eliminates y)
These two choices are B and A, respectively, so the one that does NOT work for problem 1 is choice C, as indicated below.
__
The other problems are worked in a similar fashion.
Answer:
25
Step-by-step explanation:
Let's call the missing side (the hypotenuse) c.
c² = 7²+24² (according to the pythagorean theorem)
c= ![\sqrt{625}](https://tex.z-dn.net/?f=%5Csqrt%7B625%7D)
c=25